Contribuições em morfoanatomia foliar, fitoquímica, alelopatia e caracteres farmacognósticos preliminares de Piper marginatum Jacq. (Piperaceae), de Itacoatiara, médio Rio Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Plant knowledge has always been useful to humanity, which is increasingly technological, has deepened its studies of plant resources to be sustainable. Bioactive plant phytochemicals are a promising source to be explored, and among them, many plant compounds of the genus Piper (Piperaceae) have been identified. Piper has ecological, economic and therapeutic importance. Its about 2,000 species have complex taxonomy, and errors in identification and use are common. Therefore, there is a need for a better characterization of the species of this genus. Piper marginatum Jacq. is widely used in traditional medicine. Among its classes of metabolites are terpenoids, phenylpropanoids and flavonoids, possessing properties like antifungal and antimicrobial, however there are no studies in allelopathy. This study investigated morphological and histochemical patterns of P. marginatum leaf and its phytochemical, allelopathic and antibacterial potentials. P. marginatum leaves were collected and fixed in the field and submitted to morphological and histochemical analysis, following classical methods. Extract from the leaves and their fractions were obtained to evaluate the phytochemical profile by colorimetric assays and in High Performance Liquid Chromatography. The allelopathic potential of the extract and fractions was investigated by measures of germination and growth, and antibacterial activity by disk diffusion. P. marginatum has typicall cordate shape with ciliated margin composed by tector trichomes, and the presence of two types of secretory idioblasts seems to be potential traits to their differentiation. These morphoanatomical characters has taxonomical potential and reinforce their proximity with other species of the genus. The histochemical results proved the prodution of phenolic compunds, alkaloids, polysaccharides and essential oils in the P. marginatum leaves. The crude extract (EB) yielded 3.03%; hexane fraction (FH): 31.13%, chloroform fraction (FC): 1.25%, and ethyl acetate fraction (FA): 0.97%. In phytochemistry were found phenolic compounds, flavonoids, tannins, anthocyanidins and phytosterols. Proven allelopathic activity of the crude extract and fractions significantly influenced the Germination Speed Index and the growth of the tested species, especially at concentrations of 500 μg/mL. The strains of bacteria tested were not sensitive to the samples of this work. The flavonoid vitexin was identified. Thus, the contributions of this work are a potential aid to taxonomy and phytochemistry, as well as a significant parameter for future studies on allelopathy and other biological activities in P. marginatum. Additionally, botanical findings and pharmacognostic data provide parameters for the quality control of phytotherapic potentials, as well as being able to assist in studies of safe use of medicinal plants by native peoples.
Contributions in leaf morphoanatomy, phytochemistry, allelopathy and preliminary pharmacognostic characters of Piper marginatum Jacq. (Piperaceae), from Itacoatiara, Middle Amazon River
Keywords: Germinação; Fenóis; Plantas; CIENCIAS BIOLOGICAS: BOTANICA; CIENCIAS AGRARIAS: AGRONOMIA; aleloquímicos; germinação e crescimento; Amazônia; compostos fenólicos; idioblastos secretores; vitexina